Rueful death a China Bayles mystery - Albert, Susan Wittig (New York : Berkeley Prime Crime, 1997)
In search of respite, China takes off to St. Theresa's Monastery with her friend Maggie, a former nun. The goal is a brief, tranquil retreat$1 (Bbut there's a conflict at the convent. The mother superior has recently died, and a battle over the future of St. Theresa's suggests that her sudden demise might not have been accidental. Now, China's quest for a replenished spirit takes second place to a more earthbound pursuit: catching a killer...s
"A Berkley Prime Crime book."
Includes bibliographical references.
73377
Keywords: Bayles, China (Fictitious character) -- Fiction; Women detectives -- Fiction. -- Texas; Herbalists -- Fiction. -- Texas; Texas -- Fiction; Detective and mystery stories